The impact of learning assistant facilitation practices on student in-the-moment learning - Nicolette M. Maggiore; Kataleeya P. Powers; Krystal L. Lwanga; Ira Caspari-Gnann (SpringerOpen, 2024)
Abstract Background Learning assistants (LAs) in undergraduate STEM lectures facilitate discussions between students in small groups. In this research study, we investigate the impact of LA facilitation on student learning as it occurs during LA-student interactions. To do so, our work builds on two sociocultural frameworks focused on LA facilitation and student in-the-moment learning. We conceptualize LA facilitation as either authoritative if it centers one perspective or dialogic if it centers multiple perspectives. Student in-the-moment learning is understood as the progression of student needs and the filling of those needs with LA and student ideas. Results Our analysis of 78 video recordings of LA-student interactions from 37 different chemistry and physics LAs revealed that LA facilitation had four major impacts on student in-the-moment learning: increasing grappling, reaching closure, sharing ideas and reasoning, and revisiting an earlier need. Rather than these impacts differing upon the use of authoritative and dialogic facilitation, all four impacts sometimes resulted from authoritative and sometimes from dialogic facilitation. However, authoritative facilitation was more often correlated with LA-centered manifestation of these impacts, while dialogic facilitation was more often correlated with student-centered manifestation. In addition to these conceptual impacts, we also found five socioemotional impacts: less participation, dominance continues, fostering participation, students choose not to participate, and lighthearted conversation. LAs added socioemotional components to both authoritative and dialogic facilitation, and actions aimed at bringing more students into the conversation indeed had this impact, while actions addressing specific students often continued to privilege the participation of the same students. Conclusion Our study expands theory on authoritativeness and dialogicity as it empirically validates that authoritative facilitation is more often correlated with LA-centered learning and dialogic facilitation is more often correlated with student-centered learning. Further, our work is the first to explore the socioemotional impact of LAs in the moment of interaction. Our findings can be used in LA trainings to teach LAs how to intentionally use authoritative and dialogic facilitation, how to incorporate socioemotional components to their facilitation, and how to adjust their practice to align with learning goals for students in their context.